Corrosion analysis of nickel and gold plated carbon steel ornamentals in sulphuric acid meduim (2012)
This study investigated the corrosion resistance of Nickel and Gold plated carbon steels ornamentals in 0.5mol/dm3Suphuric acid(H2SO4) medium. Nickel plating of carbon steel was done in watts solution for 25minutes with a current density of 3 A/dm3 at 60oC. The nickel plated carbon steel was later gold plated for 20 minutes with a current density of 0.2A/dm3 at 50oC.The plated and unplated carbon steels were exposed to H2SO4 environment for 15 days. The weight loss was taken every 24 hours in order to evaluate corrosion penetration rate(CPR). The results obtained showed that plated carbon steel generally offered a better corrosion resistance than the unplated carbon steels. The conclusion that can be drawn from this study is that Nickel plated carbon steel is found to be more reliable material to be used as ornamentals than gold plated carbon steel in H2SO4 enviroment